Rouge wave solutions of a nonlinear pseudo-parabolic physical model through the advance exponential expansion method - Habibul Bashar, Md.; Mamunur Roshid, Md. (International Journal of Physical Research, 2020)
In this work, we decide the proliferation of nonlinear voyaging wave answers for the dominant nonlinear pseudo-parabolic physical model through the (1+1)-dimensional Oskolkov equation. With the assistance of the advance -expansion strategy compilation of disguise adaptation an innovative version of interacting analytical solutions regarding, hyperbolic and trigonometric function with some refreshing parameters. We analyze the behavior of these solutions of Oskolkov equations for the specific values of the reared parameters such as rouge wave, multi solution, breather wave bell and kink shape etc. The dynamics nonlinear wave solution is examined and demonstrated in 3-D and 2-D plots with specific values of the perplexing parameters are plotted. The advance -expansion method solid treatment for looking through fundamental nonlinear waves that advance assortment of dynamic models emerges in engineering fields.Â Â